Association between oxidative stress and metabolic-associated fatty liver disease in the US population - Linyin Huang; Shifang Qu; Xinyu Cui; Yujin Jin; Yan Yao (Scientific Reports)
Abstract Limited research have been conducted on the interrelationship and role of oxidative stress and Metabolic Associated Fatty Liver Disease (MAFLD) within the population. The Oxidative Balance Score (OBS) serves as a metric for evaluating an individual’s overall oxidative stress status. This study seeks to investigate the impact of OBS on the population and elucidate its potential mechanisms. 9881 participants from the 2003–2018 NHANES were involved in our study. Covariate-adjusted regression models showed a statistically significant inverse association between elevated OBS and MAFLD risk. Specifically, participants in the upper threshold quartile (Q4) had 40% lower risk of MAFLD odds (OR = 0.60, 95% CI 0.50–0.72; P < 0.001) compared to those in the lowest reference quartile (Q1). The population attributable fraction analysis (PAF) suggested that MAFLD reduction could be attributed to approximately 12.67% Q4 OBS and 8.00% Q3 OBS. Restricted cubic spline (RCS) analysis revealed a non-linear association between oxidative balance score OBS and MAFLD. In the mediation analysis, inflammatory markers, insulin resistance markers, and body mass index (BMI) were found to partially mediate the association between OBS and MAFLD. The continuous OBS (HR: 0.97, 95% CI (0.94, 1.00); P = 0.049) demonstrated a reduced risk of total mortality among MAFLD patients. In the U.S. population, significant negative associations were observed between OBS and MAFLD. The results indicated that an antioxidant lifestyle may hold greater significance than an antioxidant diet in the prevention of MAFLD. Additionally, our findings implied that insulin resistance, inflammation, and BMI may contribute to the relationship between OBS and MAFLD.